MEMBANGUN KESADARAN AKAN BAHAYA JUDI ONLINE DI KALANGAN REMAJA DI INDONESIA - Heri Sulesmono; Adi Nur Rohman (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2025)
The more human life develops in this world, the faster and more unpredictable the development of science and technology systems (IPTEK) will be in bringing changes to life in society. The quality and creativity possessed by humans encourage to further increase discoveries in various fields, one of which is in the field of technology. The internet does provide convenience for human life. However, with the development of the era, many uses of the internet are increasingly easy to misuse by certain parties who are solely looking for profit. One of the influences of progress in the field of technology and communication today is in gambling games that are played online or commonly called online gambling. With the rapid development of the era, gambling is increasingly improvising. Gambling that used to be played directly has now begun to be abandoned by gamblers and they have started to switch to online gambling which is increasingly popular. Because online gambling itself offers various types and easy access for its users. Online gambling, often known as cyber gambling, is a type of game that is played online using a computer or smartphone that is accessed via an internet connection.